Which factors distinguish the different consumer segments of green fast-moving consumer goods in Germany? - Andreas Niedermeier; Agnes Emberger-Klein; Klaus Menrad (Business Strategy and the Environment, 2021)
Consumer segmentation is an important tool for dealing with the often strongly differing consumer preferences in many markets for fast-moving consumer goods. Therefore, this study analyses the factors that can distinguish the different consumer segments for green all-purpose adhesives in Germany. On the basis of an online survey with 709 respondents, we performed a choice experiment and segmented consumers based on their preferences for this product. We identified six consumer segments of which in particular Green Consumer Value, Perceived Consumer Effectiveness and Trust separate eco-friendly consumers from the other groups. Our results give a deeper insight into the different consumer segments for green fast-moving consumer goods and facilitate the development of business and marketing strategies in a more targeted way.
Keywords: 330; choice experiment; consumer segmentation; green fast-moving consumer goods; influencing factors